The relationship between age of menarche and duration of menstruation with the incidence of primary dysmenorrhea - Lestari Sudaryanti; Sri Ratna Dwiningsih; -, Nur Mulyani (Journal of Health Education and Literacy, 2022)
Dysmenorrhea causes a decrease in women's quality of life. The incidence of primary dysmenorrhea in Indonesia reaches 56.4%. The purpose of this study was to examine the relationship between age of menarche and duration of menstruation on the incidence of dysmenorrhea. This type of research is quantitative with an observational analysis design using a cross-sectional approach. Data collection in this study was carried out using a questionnaire distributed online in the form of a google form. The analysis used in this study is the univariate analysis and bivariate analysis using the Chi-Square test. The results of the analysis show that there is a relationship between the age of menarche and the incidence of dysmenorrhea with a P-Value of 0.016, and the results of the analysis show that there is a relationship between the length of menstruation and the incidence of dysmenorrhea with a P-value of 0.024. So it can be concluded that there is a significant relationship between the age of menarche and the length of menstruation with the incidence of primary dysmenorrhea. Thus, efforts to overcome menstrual pain are by avoiding stressors, doing regular exercise and consuming foods with balanced nutrition, avoiding caffeinated foods and drinks, and consuming lots of mineral water.